238 Colorectal Cancer Surveillance In IBD: An Audit of a Large NHS Healthcare Trust. (4th May 2021) - Claxton, H; Johnson, C
Abstract: Aim: To investigate compliance with endoscopic screening guidelines for patients with Inflammatory bowel disease (IBD) in a large English Foundation Trust. Method: A database of pathology specimens coded with a diagnosis of IBD since 2012, was cross-referenced with trust-wide colorectal cancer database. NICE guidelines (2011) provided audit standard: Low risk require 5 yearly, moderate risk 3 yearly, and high-risk yearly colonoscopies. A randomised sample of IBD patients (n = 50) and all patients with both IBD and colorectal cancer (n = 4) were compared to this standard. Results: Compliance to the audit standard within the population (n = 54) was only 50%, and only 25% within sub-group with both IBD and Colorectal cancer (n = 4). Conclusions: Only 4 cases of colorectal cancer within our IBD population were on record since 2012, suggesting incomplete patient identification, perhaps due to unreliable coding. The importance of optimising cancer screening programmes has only increased following the burden of the COVID-19 pandemic. Compliance within the audit population (n = 54) was only 50%, these findings promote a review of the screening process within the trust and advocate further complementary audits of additional NHS healthcare trusts.